If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 4)(x + -6) = 0 Reorder the terms: (4 + 2x)(x + -6) = 0 Reorder the terms: (4 + 2x)(-6 + x) = 0 Multiply (4 + 2x) * (-6 + x) (4(-6 + x) + 2x * (-6 + x)) = 0 ((-6 * 4 + x * 4) + 2x * (-6 + x)) = 0 ((-24 + 4x) + 2x * (-6 + x)) = 0 (-24 + 4x + (-6 * 2x + x * 2x)) = 0 (-24 + 4x + (-12x + 2x2)) = 0 Combine like terms: 4x + -12x = -8x (-24 + -8x + 2x2) = 0 Solving -24 + -8x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-12 + -4x + x2) = 0 Factor a trinomial. 2((-2 + -1x)(6 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {-2, 6}
| x-2=-27 | | -22=6(2(-5.33)+7) | | 3x+8y-6z=24 | | 2x=20+20 | | k/-3-11 | | -5n+8=-07 | | 6(2(5.33)+7)= | | F(x)=7x^3 | | 4(2x-5)=120 | | -49x^2=-64 | | y=0.0002x^3-0.04x^2+2x | | 4x-26=3x | | 2w+1l= | | -22=6(2k+7) | | 50-80+30=-60 | | n^2-n-93=0 | | u=135+396 | | 72.5+-101.5= | | 3(2x+4)=2x+20 | | -20+32x=-1140 | | n^2-n-21=72 | | 12+2x=x+6 | | 0.7b+5=20-b | | Y+3=m(x+5) | | 300= | | 3.50*x=18.25 | | (3x-7)=(2y+2) | | 3(2y+3)-2(y+5)= | | -6c+5=13 | | 365x=260x | | n+3xn+3-10=72 | | -29=-5f+7f |